Students’ learning preferences in a multimedia online course - Kišiček, Sanja; Golubić, Kruno; Lauc, Tomislava (2012)
This paper presents the results of a research on the usage of multimedia resources with respect to learning styles. The research was conducted within an online course supporting multimedia resources. The course is s fully online elective course in the field of Information Sciences, offered to all students at the Faculty of Humanities and Social Sciences at the University of Zagreb, Croatia. The content of the course is offered in the form of interactive Moodle lessons containing three different types of multimedia resources: textual, pictorial resources accompanied by text and video resources. By analyzing the results of a VARK questionnaire, which label the students’ learning styles as visual, aural, read/write and kinesthetic, and matching them with the results of students’ feedback responses indicating what type of resources the students have been using, we determine on the relationship between learning styles and preferences. Students with stressed visual learning style show lesser preferences towards the usage of textual resources. Students with stressed read/write learning style show lesser preferences towards the usage of video resources. Understanding the learners’ preferences leads to more effective instructional design in an online learning environment.
ENG